Obituaries, newspaper cuttings, typescript speeches and commemorations relating to deceased members of the I.R.A. (N - R) - O'Donoghue, Florence, 1895-1967 (1954)
Material relates to Timothy J. Nolan (Jan. 1958), William O’Brien (Nov. 1916), Seosamh Ó Ceannaigh (24 May 1954), Donnchadha O’Hannigan (Aug. 1962), Eugene O’Neill (May 1959) and Frank Ryan (July 1965).
Keywords: Irish Republican Army; Ireland -- History -- 1922-